Behavior and clinical impact of ascites after living donor liver transplantation: risk factors associated with massive ascites. (4th September 2016) - Ito, Daisuke; Akamatsu, Nobuhisa; Togashi, Junichi; Kaneko, Junichi; Arita, Junichi; Hasegawa, Kiyoshi; Sakamoto, Yoshihiro; Kokudo, Norihiro
Abstract: Background: Massive ascites after living donor liver transplantation (LDLT), defined as small‐for‐size graft syndrome, is a risk factor for a poor prognosis. Few studies have reported factors associated with ascites and the relevant outcome after LDLT. Methods: Data from 413 adult patients that underwent LDLT were retrospectively analyzed. Results: Recipient age, preoperative albumin level, Child–Pugh score, preoperative ascites, graft volume, intraoperative blood loss, and duration of warm ischemic time and the anhepatic phase were significantly associated with the total amount of ascites between postoperative day (POD) 1 and POD14. Multivariate analysis identified preoperative ascites, intraoperative blood loss, and duration of anhepatic phase as factors. Massive ascites (ascitic fluid discharge >1, 000 ml/day on POD14 after LDLT) occurred in 200 (48.4%) patients, and mild ascites occurred in the remaining 213 patients. Daily changes in the ascites volume differed between the two groups. Nevertheless, massive ascites itself did not have a critical impact on the patient short‐ and long‐term outcomes when properly managed with rigorous diuretics and albumin administration. Conclusion: Massive ascites is frequent after LDLT; however, the impact of it could be minimized with an appropriate management. Abstract : Ito and colleagues investigated the clinical characteristics of postoperative ascites after living donor liver transplantation. The risk factors for massive ascites after living donor liver transplantation were preoperative ascites, intraoperative blood loss, and duration of the anhepatic phase. If properly managed, however, massive ascites will not affect the recipient's prognosis.